2023
DOI: 10.1017/s0025315422000996
|View full text |Cite
|
Sign up to set email alerts
|

Teratological records in blue shark Prionace glauca embryos from the South-western Atlantic Ocean

Abstract: Abnormal embryonic development may result from mutations caused by genetics, environmental conditions or viruses. This study reports cases of cyclopia and a mouth malformation in two embryonic blue shark Prionace glauca collected off southern Brazil (South-western Atlantic). Such malformations are likely to reduce the chances of survival of embryos and neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Various teratological conditions have been reported in chondrichthyans, including bicephaly (Bornatowski & Abilhoa, 2009; Galván‐Magaña et al, 2011; Guida et al, 2013; Muñoz‐Osorio et al, 2013; Prado et al, 2020), cyclopia (Cabanillas‐Torpoco et al, 2023), anophthalmia (Ehemann et al, 2022; Rolim et al, 2020), albinism (Clark, 2002; Sandoval‐CaStillo et al, 2006), and assorted skeletal deformities (Bonfil, 1989; Moore, 2015; Wosnick et al, 2019; Zaera & Johnsen, 2011). Malfusion of the pectoral fins and head is one of the more commonly reported teratological conditions in the batoid elasmobranchs (Batoidea) (Ehemann et al, 2022), and the rostral malformation observed here is similar to occurrences in Rogers' round ray Urotrygon rogersi (Jordan & Starks 1895) (Mejía‐Falla et al, 2011) and Kuhl's maskray Neotrygon kuhlii (Müller & Henle 1841) (Ranjith et al, 2019).…”
Section: Figurementioning
confidence: 99%
“…Various teratological conditions have been reported in chondrichthyans, including bicephaly (Bornatowski & Abilhoa, 2009; Galván‐Magaña et al, 2011; Guida et al, 2013; Muñoz‐Osorio et al, 2013; Prado et al, 2020), cyclopia (Cabanillas‐Torpoco et al, 2023), anophthalmia (Ehemann et al, 2022; Rolim et al, 2020), albinism (Clark, 2002; Sandoval‐CaStillo et al, 2006), and assorted skeletal deformities (Bonfil, 1989; Moore, 2015; Wosnick et al, 2019; Zaera & Johnsen, 2011). Malfusion of the pectoral fins and head is one of the more commonly reported teratological conditions in the batoid elasmobranchs (Batoidea) (Ehemann et al, 2022), and the rostral malformation observed here is similar to occurrences in Rogers' round ray Urotrygon rogersi (Jordan & Starks 1895) (Mejía‐Falla et al, 2011) and Kuhl's maskray Neotrygon kuhlii (Müller & Henle 1841) (Ranjith et al, 2019).…”
Section: Figurementioning
confidence: 99%